The Role of E-Learning in Promoting the Use of Learning Organization Strategies by Al-Azhar and Islamic Universities from the Faculty Members' Perspective - Mahmoud AbdelMajeed Assaf (University of Science and Technology, Yemen, 2019)
This study aimed to identify the role of e-learning in enhancing the practice of learning organization strategies by Palestinian universities (Al-Azhar - Islamic) in Gaza governorates from the point of view of the faculty members, and to find out if there were statistically significant differences between the means of their assessment scores attributed to the study variables: (University - Years of Service - Academic Rank). To achieve these objectives, the descriptive, analytical method was used by administering a questionnaire consisting of (50) items and divided into four areas. The study sample consisted of (100) faculty members from the two universities. The results showed that the total score of the role of e-learning in enhancing the practice of learning organization strategies by Palestinian universities was medium with a relative weight of (76.6%). The first area (quality and support of education) ranked first with a relative weight of 78.6%. The third area (competitive feature and collaborative learning) was given the last rank with a relative weight of (73.0%). There were no statistically significant differences at the level of significance )α≤0.05) between the mean scores of the study respondents regarding the role of e-learning in enhancing the practice of learning organization strategies by the Palestinian universities attributed to all the study variables: (college, university, years of service and academic rank). It was recommended that specialists in the field of e-learning should be appointed in each of the colleges of the university whose task would be to overcome the obstacles, and to strengthen faculty members' competence in the field of electronic self-learning techniques, and to contribute to the production of knowledge.